SPECIFICATION A MODEL FOR STUDY OF POLITICAL RATIONALITY - García Lirios, Cruz (Sociedade e Território, 2021)
The objective of this document has been to conceptually analyze Sustainable Development. In this sense, seven concepts were chosen, based on their similarities and differences, to interpret the nature-society relationship in terms of the equitable availability of resources between species and generations. This conceptual analysis of Sustainable Development will allow us to glimpse theories, diagnoses and interventions to promote rational lifestyles favorable to the conservation of the environment.